2017
DOI: 10.1074/jbc.m116.771121
|View full text |Cite
|
Sign up to set email alerts
|

Intersubunit physical couplings fostered by the left flipper domain facilitate channel opening of P2X4 receptors

Abstract: P2X receptors are ATP-gated trimeric channels with important roles in diverse pathophysiological functions. A detailed understanding of the mechanism underlying the gating process of these receptors is thus fundamentally important and may open new therapeutic avenues. The left flipper (LF) domain of the P2X receptors is a flexible loop structure, and its coordinated motions together with the dorsal fin (DF) domain are crucial for the channel gating of the P2X receptors. However, the mechanism underlying the cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 63 publications
0
21
0
Order By: Relevance
“…The crystal structures for the open states of P2X4 and P2X3 receptors clearly show a downward shift of the LF domain toward the LB−DF domain of the neighboring subunit compared with the structures at the apo state, suggesting that the downward motion of the LF domain upon ATP binding may constitute an important step of P2X channel gating by its endogenous ligand, ATP (9)(10)(11). Previously, combining computational stimulation and mutational studies, we showed that manipulations that prevented the motion between the LF and DF domains all disrupted ATP gating of P2X4 (23,27). Not surprisingly, by allowing a disulfide bond formation between the LF and DF domains of P2X3, the activation of P2X3 K201C/V274C by ATP was also largely suppressed (34).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…The crystal structures for the open states of P2X4 and P2X3 receptors clearly show a downward shift of the LF domain toward the LB−DF domain of the neighboring subunit compared with the structures at the apo state, suggesting that the downward motion of the LF domain upon ATP binding may constitute an important step of P2X channel gating by its endogenous ligand, ATP (9)(10)(11). Previously, combining computational stimulation and mutational studies, we showed that manipulations that prevented the motion between the LF and DF domains all disrupted ATP gating of P2X4 (23,27). Not surprisingly, by allowing a disulfide bond formation between the LF and DF domains of P2X3, the activation of P2X3 K201C/V274C by ATP was also largely suppressed (34).…”
Section: Discussionmentioning
confidence: 91%
“…Furthermore, the salt bridge between R264 and D266 ( Fig. 2 A and B), a conserved structure at the beginning of LF domains of all P2X receptor subtypes (10,23), is crucial for holding the LF domain in place as the R264A (IC 50 = 0.72 ± 0.01 μM; Fig. 2C) and D266A (IC 50 > 30 μM; Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, this chimera increased sensitivity to ATP ∼30-fold ( Allsopp et al, 2017 ) and swapping with the equivalent region from the P2X4R increased potency ∼15-fold (this study). Movement of the left flipper has been proposed to be coupled to channel gating upon ATP binding ( Zhao et al, 2014 ; Karasawa and Kawate, 2016 ; Wang et al, 2017 ). Investigating the effect of individual residues in the region 279–285 reveals that the D280A mutation renders the P2X7R 15-times more sensitive to ATP.…”
Section: Discussionmentioning
confidence: 99%
“…The homology models of rP2X3 and mutants were constructed based on the hP2X3 structure (PDB ID code 5SVJ) [35] with the program MODELLER according to previous descriptions [37,38,40,41]. ClustalW2 was used to align and manually adjust the target sequences to match published alignments [35].…”
Section: Homology Modelingmentioning
confidence: 99%